Evaluation of the performance of Pléiades Neo and Sentinel-2 Satellite Imagery for Chlorophyll-a Detection - A. Tuzcu Kokal; G. N. Karal Nesil; N. Olgun Kıyak; M. Yanalak; N. Musaoğlu (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Assessing chlorophyll-a (Chla), which is an indicator of algal biomass, is important for monitoring water quality and protecting natural resources. Today’s technology enables the acquisition of high-resolution satellite imagery allowing for detailed observation of Chla levels even in small scaled water bodies such as ponds. In this study, the spatial distribution of Chla in a pond located at the Istanbul Technical University (ITU) Campus with an area of about 1.9 ha was assessed by using both high-resolution (Pléiades Neo) and medium-resolution (Sentinel-2) satellite imagery, along with in situ measurements. Pléiades Neo and Sentinel-2 and satellite images were acquired on June 10 and 11, 2024. Normalized Difference Chlorophyll Index (NDCI) was applied to images to determine Chla levels in the pond. Linear regression analysis was performed to retrieve Chla concentration values from NDCI values. The results showed that Chla concentrations ranged 16.38 – 23.83 mg/m3 based on in situ measurements, 16.52 – 23.75 mg/m3 based on Pléiades Neo data and 15.49 – 23.74 mg/m3 based on Sentinel-2 data. Both Pléiades Neo and Sentinel-2 data were consistent with in situ Chla measurements. Using high-resolution Pléiades Neo imagery, the detailed spatial distribution of Chla was determined. Based on the satellite data, higher Chla concentrations on the southern and southwestern shores of the pond. This research presents a practical approach for evaluating Chla levels within ponds, leveraging medium- and very high-resolution satellite images and the methodology can be used for water quality monitoring in small scale aquatic environments.